Network structure and centralization tendencies in professional football teams from Spanish La Liga and English Premier Leagues - Clemente, F. M.; Jose, F.; Oliveira, N.; Lourenco Martins, F. M.; Sousa Mendes, R.; Figueiredo, A. J.; Wong, D. P.; Kalamaras D. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to analyse the variance of different competitive leagues, score status, and tactical position in the centrality levels of degree prestige, degree centrality and page rank in football players. A total of 20 matches from the Spanish La Liga League (10 matches) and English Premier League (10 matches) were analysed and codified in this study. In this study only the top four teams and their opponents per each competitive league were analysed. A total of 14,738 passes between teammates were recorded and processed. The multivariate MANOVA revealed statistical differences in centrality among tactical positions (Lambda = 0.958; F(15,1212) = 37.898; p-value = 0.001; = 0.319; Moderate Effect Size). Midfielders had the greatest centrality values, followed by the external and central defenders. The lowest values of centrality were found in goalkeepers and forwards. No statistical differences were found in centrality between different competitive leagues (Lambda = 0.001; F(3,402) = 0.050; p-value = 0.985; = 0.001; Very Small Effect Size) and score status (Lambda = 0.003; F(6,806) = 0.175; p-value = 0.983; = 0.001; Very Small Effect Size).